Korelasi Rasio Aspartate Aminotransferase - Alanine Aminotransferase dengan Profil Hematologi pada Peminum Alkohol - Lucia Sincu Gunawan (Biomedika, 2019)
Toxicity due to alcohol is the most common cause of liver disease and ranks health resources worldwide. In developed countries, alcohol is the main cause of cirrhosis (PalP and Ray S, 2016). People who consumes a lot of alcohol will tend to have haematological dan bone marrow’s problems, where blood is produced. The bad effects of alcohol on blood cell production occur directly or indirectly. The direct effects of excessive alcohol consumption are toxic effects on the bone marrow, red blood cells, mature erythrocyte cells, leukocytes and platelets. The indirect effect of alcohol consumption is a nutritional deficiency that can disturb production and function of various blood cells. (Ifeanyi O.E, et al, 2014). In this study, the levels of aspartate aminotransferase (AST), alanine aminotransferase (ALT), haemoglobin, erythrocytescounts, leukocytes counts, platelet counts, haematocrit and Protrombine Time (PT) and Activated Partial Thromboplastin Time (APTT) in 30 alcoholic malesat 20-50 years old were examined. From 30 respondents, haemoglobin data, the number of erythrocytes, the number of leukocytes, the number of platelets, haematocrit, PT, aPTT, AST, ALT were obtained and the ratio was also calculated. The results of the Spearman test, the AST/ALT ratio data with haemoglobin levels (p = 0.741), AST/ALT ratio with erythrocyte count (p = 0.778), AST/ALT ratio with leukocyte count (p = 0.472), AST/ALT ratio with platelet count (p = 0.95), AST/ALT ratio with haematocrit (p = 0.88), AST/ALT ratio with PT (p = 0.757), AST/ALT ratio with aPTT (0.352). There was no significant difference between the AST/ALT ratio and the haematological profile in alcohol drinkers (p> 0.05). The importance of paying attention to diet as part of a disease prevention.